1976
DOI: 10.1111/j.1751-1097.1976.tb07254.x
|View full text |Cite
|
Sign up to set email alerts
|

IN VIVO INDUCTION OF 4‐THIOURIDINE‐CYTIDINE ADDUCTS IN tRNA OF E. COLI B/r BY NEAR‐ULTRAVIOLET RADIATION*

Abstract: Abstract— Near‐ultraviolet (near‐UV; 320–405 nm) irradiation of Escherichia coli B/r induces the formation in vivo of 4Srd‐Cyd adducts in transfer RNA, as evidenced by (1) fluorescence spectrum changes of tRNA extracted from irradiated cells and reduced with NaBH4, (2) thin‐layer chromatography on cellulose of hydrolysates of trichloroacetic acid‐precipitable extracts of irradiated cells, and (3) comparison of these findings with adduct formation induced by near‐UV irradiation of purified mixed tRNA from E. co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…The sulfur atoms of thiamin, lipoic acid, biotin, iron-sulfur (FeS) 2 clusters, and molybdenum cofactors participate in stabilizing reaction intermediates (1,2), alternating between the reduced dithiol and oxidized disulfide, facilitating electron transfer, or modulating the redox potential of the cofactor (3). The thionucleosides in tRNAs fine-tune the efficiency or accuracy of translation (4,5), serve as recognition sites for aminoacyl-tRNA synthetase (6), or act as photosensors (7). Despite the diverse chemical environments in which the sulfur atoms reside in cofactors and thionucleosides, it has been found that the incorporation of sulfur into them involves a few enzymes with the persulfide (R-S-SH) groups on the cysteine residues of these enzymes; thus, these enzymes act as the key agents of sulfur transfer (8,9).…”
mentioning
confidence: 99%
“…The sulfur atoms of thiamin, lipoic acid, biotin, iron-sulfur (FeS) 2 clusters, and molybdenum cofactors participate in stabilizing reaction intermediates (1,2), alternating between the reduced dithiol and oxidized disulfide, facilitating electron transfer, or modulating the redox potential of the cofactor (3). The thionucleosides in tRNAs fine-tune the efficiency or accuracy of translation (4,5), serve as recognition sites for aminoacyl-tRNA synthetase (6), or act as photosensors (7). Despite the diverse chemical environments in which the sulfur atoms reside in cofactors and thionucleosides, it has been found that the incorporation of sulfur into them involves a few enzymes with the persulfide (R-S-SH) groups on the cysteine residues of these enzymes; thus, these enzymes act as the key agents of sulfur transfer (8,9).…”
mentioning
confidence: 99%
“…these workers proceeded to show that ( 1 ) near-UV irradiation has a considerably sharper effect on RNA accumulation than on DNA or protein accumulation, and the action spectra for growth delay and for suppression of RNA accumulation are similar to the absorption spectrum of 4-thiouracil in transfer RNA [30], (2) near-UVinduced growth delay occurs only in E. coli strains showing a stringent control of RNA synthesis (rel' strains). and only in these strains are the levels of guanosine tetraphosphate elevated after near-UV irradiation [32], and (3) fluences effective in near-UVinduced growth delay also induce the 4Srd-Cyd adduct in the tRNA of E. colt in uiuo in amounts sufficient to account for this adduct being the lesion that leads to the growth delay [33]. These findings strongly support the interpretation that near UV induces the 4Srd-Cyd adduct in tRNA, which lowers the amino-acylating activity of many of the E. coli tRNA's, which in turn is interpreted by the cell as a partial amino acid starvation, with consequent rise in levels of guanosine tetraphosphate and sharp shutoff of RNA accumulation.…”
Section: Tvansient Effects On Cellsmentioning
confidence: 99%
“…An important source of oxidative stress for bacteria in environments exposed to sun light is near UV irradiation (300-400 nm), which corresponds to the sun irradiation with highest energy that can cross the atmosphere [58]. Near UV irradiation of bacteria like E. coli, Salmonella Thyphimurium or Enterobacter cloacae produces growth arrest which depends mainly in the photochemical oxidation of the tRNA modified base 4-thiouridine (s 4 U) present in position 8 of all tRNAs [39][40][41][42]. In some tRNAs that also have a C in position 13 (50% of bulk tRNA) an internal crosslinking reaction happens that produces 5-(4´-pyrimidin 2´-one) [39,40,59].…”
Section: Oxidation Of Trnamentioning
confidence: 99%
“…Near UV irradiation of bacteria like E. coli, Salmonella Thyphimurium or Enterobacter cloacae produces growth arrest which depends mainly in the photochemical oxidation of the tRNA modified base 4-thiouridine (s 4 U) present in position 8 of all tRNAs [39][40][41][42]. In some tRNAs that also have a C in position 13 (50% of bulk tRNA) an internal crosslinking reaction happens that produces 5-(4´-pyrimidin 2´-one) [39,40,59]. Some cross-linked tRNAs have been shown to be poor substrates for aminoacylation [40,60,61] and in some cases also for translation [60].…”
Section: Oxidation Of Trnamentioning
confidence: 99%
See 1 more Smart Citation